Implementasi Manajemen Riayah dalam Meningkatkan Kenyamanan Jamaah - Nurhayati, Nurhayati; Rahman, Arif; Setiawan, Asep Iwan (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to find out the riot planning at the Cipaganti Grand Mosque in increasing the comfort of pilgrims, to find out the application of riayah at the Cipaganti Great Mosque in increasing the comfort of worshipers, to find out the evaluation of riayah at the Cipaganti Great Mosque in increasing the comfort of worshipers. This study uses the descriptive method with a qualitative approach. The techniques in collecting data through observation, interviews and documentation studies as evidence of riayah’s management in an effort to improve the comfort of pilgrims at the Cipaganti Grand Mosque. Based on the results of research conducted at the Cipaganti Grand Mosque from the implementation of riayah management in improving the comfort of pilgrims it can be concluded: First, that the planning of riayah in the Great Mosque of Cipaganti formulates work programs, facilities, and physical maintenance of the mosque. Second, that implementation means that whatever has been formulated must be implemented. Where in making work programs in accordance with the standards of mosque management so that the physical maintenance of the mosque can be directed and run in accordance with expectations and goals, namely to foster a sense of comfort towards worshipers. Third, that evaluation is a corrective action if the results are not as expected. So in this case the evaluation can be done in the short and long term.